Successful Management of the Fetal Severe Anemia Associated with Jra Alloimmunization by Intrauterine Transfusion of Jr(a+) Red Blood Cells - Masatake Toshimitsu; Shinichi Nagaoka; Shuusaku Kobori; Yuichiro Takahashi; Jun Murotsuki (Case Reports in Obstetrics and Gynecology)
Objective. We present a case of fetal severe anemia associated with Jra alloimmunization, which was managed using Doppler measurement of the peak systolic velocity of the fetal middle cerebral artery (MCA-PSV) and intrauterine transfusion (IUT) of Jr(a+) red blood cells (RBCs). We also review the previous case reports on fetal or neonatal anemia associated with Jra alloimmunization. Case Report. A woman with Jra alloimmunization was referred to our department at 29 weeks of gestation. As fetal MCA-PSV exceeded 1.55 multiples of the median, fetal blood sampling was performed and demonstrated severe anemia. During the course, a total of two IUTs were performed using Jr(a+) RBCs. The neonate was delivered by repeated cesarean section at 35 weeks of gestation and showed no apparent signs of hemolysis. Conclusion. Based on the literature review, fetal anemia associated with Jra alloimmunization becomes severe during mid-gestation and may not develop during late gestation. The severity of fetal anemia is predicted by MCA-PSV Doppler assessment rather than the maternal anti-Jra titers. Timely IUT of Jr(a+) RBCs can help to prolong the pregnancy to term in emergency situations wherein compatible blood of Jr(a-) RBCs is not available soon.